Poverty Profiles of Sylhet City Corporation: An MPI Approach - Faruque Uddin, Mohammed; Nazmul Huda, Syed (European Scientific Journal, ESJ, 2016)
Does income measure of poverty explain it meticulously? To seek this answer we claim poverty is not a unidimensional phenomenon rather it adheres multidimensionality. Sen (2000) views poverty as the deprivation of certain basic capabilities, which varies from elementary physical nourishment to the community life. However, targeting slum dwellers, this article sought to advance multidimensional poverty measures in SCC (Sylhet City Corporation). The study adopts a mixed method approach to examine so. Finding shows that, there are some variations in the percentage of poor households. In terms of income and expenditure 60% households are identified as poor but in MPI number increases to 75%. Data from in-depth interview exhibits that respondents feel themselves as income poor. Some of them consider deprivation of education is the consequence of that income poverty. In addition, few respondents dimple that health problems and physical disabilities mingle their poverty experiences.